Respiratory Sinus Arrhythmia is Mainly Driven by Central Feedforward Mechanisms in Healthy Humans - Skytioti, Maria; Elstad, Maja (Frontiers in Physiology, 2022)
Heart rate variability (HRV) has prognostic and diagnostic potential, however the mechanisms behind respiratory sinus arrhythmia (RSA), a main short-term HRV, is still not well understood. We investigated if central feedforward mechanism or pulmonary stretch reflex contributed most to RSA in healthy humans. Ventilatory support reduce the centrally-mediated respiratory effort, but remain the inspiratory stretch of the pulmonary receptors. We aimed to quantify the difference in RSA between spontaneous breathing and ventilatory support. Nineteen healthy, young subjects underwent spontaneous breathing and non-invasive intermittent positive pressure ventilation (NIV) while we recorded heart rate (HR, from ECG), mean arterial pressure (MAP) and stroke volume (SV) estimated from the non-invasive finger arterial pressure curve, end tidal CO2 (capnograph) and respiratory frequency (RF) with a stretch band. Variability was quantified by integral between 0.15-0.4 Hz calculated from the power spectra. Median and 95% confidence intervals (95%CI) were calculated as Hodges-Lehmann’s one-sample estimator. Statistical difference was calculated by Wilcoxon matched-pairs signed rank test. RF and end-tidal CO2 were unchanged by NIV. NIV reduced HR by 2 bpm, while MAP and SV was unchanged in comparison to spontaneous breathing. Variability in both HR and SV was reduced by 60% and 75%, respectively, during NIV as compared to spontaneous breathing, but their interrelationship with respiration was maintained. NIV reduced RSA through less central respiratory drive, and pulmonary stretch reflex contributed little to RSA. RSA is mainly driven by central feedforward mechanism in healthy humans. Peripheral reflexes may contribute as modifiers of RSA.